More or less political: findings on a central feature of local engagement for refugees in Germany - Schmid, Verena; Evers, Adalbert; Mildenberger, Georg (Social Inclusion, 2019)
Abstract: The article is based on research in the region of Heidelberg - the city itself and two small municipalities nearby. It addresses three dimensions of local support movements for refugees: (1) the varying bundles of motives among those engaged, (2) the diversity of organizations concerned and (3) their interaction with the local political administration. A focal point of the study concerns features and processes that give actions and organizations a more or less political character. Our results reveal that, especially among newly engaged helpers and activists, political and apolitical motives coexist. Many people and their local organizations take positions in the country-wide controversial political debates on refugees, but for their practical action on location, moral concerns clearly prevail. Processes of politicization and depoliticization of refugee support largely depend on the ways and degrees to which nationwide political controversies and local developments intermesh. Politicization may take place due to controversies that call for more than a moral attitude, have an impact and build up at the local level. However, resistance to supportive action, be it by changing discourses or the persistence of traditional administrative routines, may also cause depoliticization, where volunteers and initiatives restrict themselves to acting as mere helpers that bring some human touch into an environment that longs to return to normality.
Gesehen am 23.10.2019